Medication Regimen Complexity In 8 Australian Residential Aged Care Facilities: Impact Of Age, Length Of Stay, Comorbidity, Frailty, And Dependence In Activities Of Daily Living - Chen EYH (Dove Medical Press, 2019)
Esa YH Chen,1,2 J Simon Bell,1–3 Jenni Ilomaki,2,3 Claire Keen,1 Megan Corlis,2,4 Michelle Hogan,4 Jan Van Emden,2,4 Sarah N Hilmer,2,5 Janet K Sluggett1,2 1Centre for Medicine Use and Safety, Faculty of Pharmacy and Pharmaceutical Sciences, Monash University, Parkville, VIC, Australia; 2NHMRC Cognitive Decline Partnership Centre, Hornsby Ku-ring-gai Hospital, Hornsby, NSW, Australia; 3Department of Epidemiology and Preventive Medicine, School of Public Health and Preventative Medicine, Monash University, Melbourne, VIC, Australia; 4Helping Hand Aged Care, North Adelaide, SA, Australia; 5Kolling Institute, Faculty of Medicine and Health, The University of Sydney and Royal North Shore Hospital, St Leonards, NSW, AustraliaCorrespondence: Esa YH ChenCentre for Medicine Use and Safety, Faculty of Pharmacy and Pharmaceutical Sciences, Monash University, 381 Royal Parade, Parkville, VIC 3052, AustraliaTel +61 3 9903 9533Email Esa.Chen@monash.eduObjective: To explore variation in medication regimen complexity in residential aged care facilities (RACFs) according to resident age, length of stay, comorbidity, dementia severity, frailty, and dependence in activities of daily living (ADLs), and compare number of daily administration times and Medication Regimen Complexity Index (MRCI) as measures of regimen complexity.Methods: This study was a cross-sectional analysis of baseline data from the SImplification of Medications Prescribed to Long-tErm care Residents (SIMPLER) cluster-randomized controlled trial. The SIMPLER study recruited 242 residents with at least one medication charted for regular administration from 8 RACFs in South Australia. Comorbidity was assessed using the Charlson Comorbidity Index (CCI). Dementia severity was assessed using the Dementia Severity Rating Scale. Frailty was assessed using the FRAIL-NH scale. Dependence in ADLs was assessed using the Katz ADL scale.Results: The median age of participants was 87 years (interquartile range 81–92). Over one-third of participants (n=86, 36%) had 5 or more daily medication administration times. The number of daily administration times and MRCI scores were positively correlated with resident length of stay (rs=0.19; 0.27), FRAIL-NH score (rs=0.23; 0.34) and dependence in ADLs (rs=−0.21; −0.33) (all p<0.01). MRCI was weakly negatively correlated with CCI score (rs=−0.16; p=0.013). Neither number of daily administration times nor MRCI score were correlated with age or dementia severity. In multivariate analysis, frailty was associated with number of daily administration times (OR: 1.13, 95% CI: 1.03–1.24) and MRCI score (OR: 1.26, 95% CI: 1.13–1.41). Dementia severity was inversely associated with both multiple medication administration times (OR: 0.97, 95% CI: 0.94–0.99) and high MRCI score (OR: 0.95, 95% CI: 0.92–0.98).Conclusion: Residents with longer lengths of stay, more dependent in ADLs and most frail had the most complex medication regimens and, therefore, may benefit from targeted strategies to reduce medication regimen complexity.Keywords: Aged, nursing homes, medication regimen complexity, frailty index, activities of daily living, multimorbidity, long-term care facilities